PENGEMBANGAN LKPD BERBASIS CREATIVE PROBLEM SOLVING PADA MATERI SISTEM EKSKRESI UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA KELAS VIII SMP NEGERI 2 SAJINGAN BESAR - Sintiya Oktaviani; Mustika Sari; Herditiya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and evaluate the validity, practicality, and effectiveness of Student Worksheets (LKPD) based on Creative Problem Solving (CPS) on the Excretory System material to enhance the creative thinking skills of eighth-grade students at SMP Negeri 2 Sajingan Besar. This research is a Research and Development (R&D) study using the Hannafin and Peck development model, which consists of three main stages: need assessment, design, and development and implementation. The data collection instruments included expert validation sheets (media and material experts), student response questionnaires, and pretest-posttest creative thinking skills tests. The results demonstrated that: (1) the CPS-based worksheet was categorized as Very Valid, achieving average validity scores of 91% from media experts and 92% from material experts; (2) the worksheet was deemed Very Practical based on student response questionnaires, scoring 77% in the small-scale trial and 78% in the large-scale trial; (3) the worksheet was proven Effective in improving students' creative thinking skills, indicated by an average N-Gain score of 0.732 (High category) and supported by the Wilcoxon Signed Rank Test results (Sig. 0.000 < 0.05). Consequently, the Creative Problem Solving-based LKPD on the Excretory System is suitable, practical, and effective for use in science education to enhance students' creative thinking skills.